School education amid crisis: a secondary data analysis of cyclone Amphan and COVID-19 in North & South 24 Parganas, West Bengal - Tisha Goswami; Zafar Tabrez (Discover Global Society)
Abstract West Bengal in India is one of the worst impacted states by the cyclones. The first super cyclone after the 1999 super cyclone was in May 2020, called cyclone Amphan, which devastated West Bengal to its core, especially the North 24 Parganas and South 24 Parganas districts, where the major portion of the Indian Sundarban also lies. Its impact doubled due to the spread of COVID-19 and lockdowns all over the world. Disruptions due to these disasters and already present low standards of living turned the school education in these districts’ upside down. Therefore, this study focuses on knowing the status of the school education sector during COVID-19 and cyclone Amphan by identifying the factors that disrupted the availability of continuous quality education for the students. This study concludes on the lack of disaster resilience educational facilities and recovery options in the North 24 Parganas and South 24 Parganas, along with the Indian Sundarban, which, even after the record of facing severe cyclones, have not been improved. Further, it suggests the need for collaborations at national and international levels to solve this issue.